Modeling and Designing Clinical Sessions with Hybrid Environments in the Metaverse - Oliveira, Eder; Trevisan, Daniela; Clua, Esteban; Silva, Mônica; Mesquita, Cláudio; Cruz, Mariana; Barbosa, Renato; Simões, Marcus; Porcino, Thiago (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
The Metaverse, an immersive virtual environment enabling realtime interactions, presents a novel opportunity to enhance workflows in healthcare, particularly in clinical sessions. The necessity for immersive, collaborative, and device-friendly environments has become increasingly apparent in the age of remote work and the rapid advancement of XR technologies. This paper explored how to model and design clinical sessions using hybrid environments in the Metaverse. We considered users’ needs across diverse devices like HMDs, notebooks, and smartphones and integrated interactions available in the Metaverse. The study began by outlining the existing protocol followed by healthcare professionals during clinical sessions. Our research identified specific tasks within the clinical session process that could be improved by integrating Metaverse interactions. Based on these findings, we proposed and developed a prototype, which was evaluated by HCI, XR experts and stakeholders. Our findings provide valuable insights for healthcare professionals and Metaverse designers, pointing directions for future research.